Korelasi Penguasaan Kosakata Dengan Kemampuaan Menulis Wacana Pada Siswa Kelas XI SMA Jaya Negara - Jafar Jafar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to describe how the correlation of vocabulary mastery with the ability to write discourse in class XI SMA Jaya Negara. This research is a correlation research. From the research results show that the correlation. index "r" product moment with the magnitude of rxy (0.725). This means that there is a moderate or quite significant correlation between vocabulary mastery and discourse writing ability for class XI SMA Jaya Negara students, with a contribution of 52% while the remaining 48% is determined by other factors. This means that "there is a significant relationship between vocabulary mastery and the ability to write discourse for class XI SMA Jaya Negara students in the 2022/2023 academic year.